Combined Surface Light Scattering and Pendant-Drop Experiments for the Determination of Viscosity and Surface Tension of High-Viscosity Fluids Demonstrated for Ionic Liquids - Zhai, Ziwen; Jander, Julius Hans; Bergen, Alexander; Cui, Junwei; Meyer, Karsten; Koller, Thomas Manfred (International Journal of Thermophysics, 2022)
The present study provides a strategy for the determination of the viscosity and surface tension of high-viscosity fluids in the form of ionic liquids (ILs) at equilibrium conditions by combining surface light scattering (SLS) and the pendant-drop (PD) method within one experimental setup. Through the study of the same sample under identical conditions by both methods inside a closed system, the surface tension determined via the PD method can be directly used to evaluate the dynamics of surface fluctuations of ILs with an overdamped behavior probed by SLS for accessing their viscosity. In connection with the SLS experiments, variations in the applied detection geometries in reflection and transmission direction and in the probed wave vectors down to relatively small values were also addressed. The reliability and self-consistency of SLS and the PD method applied within the same sample cell has been proven by investigating the reference fluids tris(2-ethylhexyl) trimellitate (TOTM) and n-dodecane featuring relatively high and low viscosities. For the two studied model ILs of opaque to non-transparent color, i.e., the hydrophobic 1-methyl-3-octylimidazolium hexafluorophosphate ([OMIM][PF6]) and the hydrophilic 1,3-bis(2-(2-methoxyethoxy)ethyl)imidazolium iodide ([(mPEG2)2Im]I), the combination of PD measurements and SLS experiments in reflection direction performed at ambient pressure between (303 and 373) K allowed access to the viscosity and surface tension with typical relative expanded uncertainties of (4 and 2) %. These results agree well with own viscosity data from capillary viscometry and experimental data in the literature, demonstrating the performance of the novel approach for the contactless in-situ measurement of viscosity and surface tension of fluids with relatively high-viscosity such as ILs.
CRIS-Team Scopus Importer:2022-10-21
Keywords: Ionic liquids; Pendant-drop method; Surface light scattering; Surface tension; Viscosity